ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERTUMBUHAN EKONOMI KABUPATEN/KOTA DI PROVINSI KEPULAUAN BANGKA BELITUNG, 2005-2009 - , Oktaviany ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This study aims to analyze the influence of the General Allocation Fund (DAK), the Special Allocation Fund (DAK), government development expenditure, the proportion of high school educated labor force upward, the length of district / city roads are paved and the number of centers of economic growth in the district / city in the province Bangka Belitung Islands, as well as identify the factors, which of the factors mentioned above that have the greatest influence on economic growth in the province of Bangka Belitung Islands for the period 2005- 2009. The data used in this study is secondary data from 7 counties / cities in the province of Bangka Belitung Islands starting in 2005 until the year 2009 using regression analysis of panel data. The secondary data include: data of GDP at constant prices (base year 2000), and DAU/DAK data, government development expenditure data, labor force data by the last education attained, the data length of the road district / city, and the number of health centers. This study uses panel data, which is a combination of time series data and cross section data. The model estimated with panel data regression model specifications and tested to obtain the best model and test the classical assumptions. The results showed a variable proportion of high school educated labor force upward, the length of roads are paved and the number of HEALTH centers have a positive influence and significantly affect economic growth in the district / city in the province of Bangka Belitung period 2005-2009. Variable General Allocation Fund (DAU), Special Allocation Fund (DAK) and government development spending no significant effect on economic growth in the district / city. Factors that have the greatest influence on economic growth is the number of health centers.